CINEMA AND SCIENCE: THE HYBRID BODY - Gil, Inês (Animus. Revista Interamericana de Comunicação Midiática, 2021)
The relationship between science and cinema has not always been peaceful. If film has been fundamental to scientific and technological progress thanks to the register of movement, when cinema took over fiction, it became interested in the literary stories of mad scientists, who chose to transgress the ethical codes of their field in the name of creating a perfect humanity. Artificial genetic creation laboratories are a reality close to home today, with the insertion of human cells into animal embryos. From Dr. Moreau to contemporary research, the cinematic imagination allows us to examine the fantasies of omnipotence that easily seize researchers, and confront them with the destructive consequences of their megalomania.